Guide on the processes and partnerships for co-designing socio-technical innovation bundles for women empowerment and resilience in Ethiopia - Ketema, Dessalegn; Nchanji, Eileen; Lutomia, Cosmas; Gartaula, Hom (2024)
This executive summary documents the processes and partnerships needed in co-designing socio-technical innovation bundles for women empowerment and resilience (not forgetting men and youths) in Ethiopia. Effective and constructive documentation plays a crucial role in ensuring operational efficiency, fostering collaboration, and maintaining consistency. Additionally, establishing and nurturing strong partnerships leads to enhanced opportunities for growth and success. Documenting processes are essential for several reasons. Firstly, it enables organizations to capture the process and preserve valuable knowledge and expertise needed and engaged in co-designing and implementing Social-Technological Innovation Bundles (STIBs) for women’s empowerment and resilience in Ethiopia and elsewhere. This ensures that critical information is not lost when projects are phasing out or transitioning roles. Secondly, documented processes promote consistency and standardization, minimizing confusion and errors.